KEMAMPUAN MENYIMAK BERITA SISWA KELAS X IPS SMA NEGERI 1 O’O’U - Duho, Demetrius (Universitas Nias Raya, 2025)
This research aims to describe the ability to listen to news for class X SMA Negeri 1 O'o'u for the 2023/2024 academic year. The approach used in this research is a descriptive approach. This research data was analyzed using data reduction, verification and drawing conclusions. The results of this study show that there are still many students in the ability to listen to news in class This is because many students still lack concentration in the learning process, especially in listening to the news, and there are still many students who do not know the elements of news because the news that students hear does not match what they want. Suggestions for future researchers, the results of this research can be used as relevant research material. For students, it is hoped that this research will motivate students to be able to understand the news listening abilities of class X students at SMA Negeri 1 O'o'u. For teachers, it is hoped that this research can become learning material for students by learning to understand the ability to listen to news for class X SMA Negeri 1 O'o'u